2019
DOI: 10.5039/agraria.v14i2a5640
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in forest populations from conservation units in the Atlantic Rainforest in northeast Brazil

Abstract: Fragmentation leads to changes in the size and dynamics of forest populations. Studies of genetic diversity support strategies for preserving the genetic resources, and the data to date for the Atlantic Forest in northeast Brazil is scarce. Thus, the objective of this study was to evaluate the genetic diversity of Protium heptaphyllum (Burseraceae) tree species in three populations. We sampled 64 individuals in this study, for which seven primers used generated 90 loci, with 93% being polymorphic. The average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Polymorphism, which is considered an important measure of diversity, was different among populations and these results were lower than that observed for other tree species in the Atlantic Forest biome, such as Hancornia speciosa Gomes (Apocynaceae), with an approximate polymorphism of 81.00% based on a study of 105 individuals (Fajardo et al, 2018), and Protium heptaphyllum (Aubl.) Marchand (Burseraceae), with polymorphism of 93.00% for 64 individuals (Freire et al, 2019). In the present study we found that the managed areas have high levels of genetic diversity, thus contributing to the maintenance of the species over time.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Polymorphism, which is considered an important measure of diversity, was different among populations and these results were lower than that observed for other tree species in the Atlantic Forest biome, such as Hancornia speciosa Gomes (Apocynaceae), with an approximate polymorphism of 81.00% based on a study of 105 individuals (Fajardo et al, 2018), and Protium heptaphyllum (Aubl.) Marchand (Burseraceae), with polymorphism of 93.00% for 64 individuals (Freire et al, 2019). In the present study we found that the managed areas have high levels of genetic diversity, thus contributing to the maintenance of the species over time.…”
Section: Discussionsupporting
confidence: 55%
“…They can provide information on genetic diversity indices, allele and genotypic frequencies, gene flow, effective population size, fixation index, genetic distance, and genetic bottlenecks (Brandão et al, 2015;Costa et al, 2015). ISSRs cannot differentiate heterozygous from homozygous individuals, they have been used in studies of intra-and interpopulation genetic diversity, as well as in analyses of genetic structure Fajardo et al, 2018;Laakili et al, 2018;Bocanegra-González et al, 2019;Freire et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The pairs of individuals with the highest values of genetic identity were 13 and 15 (0.87), 17 and 19 (0.85) and 5 and 10 (0.84), which were grouped into distinct clusters, suggesting that these individuals have greater genetic similarity to each other. In the dendrogram, from a cutoff point of 0.70 of Nei's (1978) genetic identity, it is possible to identify 10 groups: G1 (1, 2, 3, 4, 5, 8 and 10); G2 (14 and 16); G3 (17, 19, 21, 23 and 24); G4 (28 and 29); G5 (20); G6 (25 and 27); G7 (26); G8 (6, 7, 9, 11, 12, 13 and 15); G9 (18 and 22) and G10 (30 The Nei's (1978) diversity index for the study population was He = 0.35 ± 0.15, while the Shannon index (I) was 0.52 ± 0.18, which can be considered low to intermediate, when compared to the results obtained in studies with the same markers for other forest species (RAJASEKHARAN et al, 2017;FREIRE et al, 2019;LOPES;COSTA;ARRIEL, 2020).…”
Section: Resultsmentioning
confidence: 67%
“…Further research is necessary, such as analyzing the acceleration of seed germination via studies of dormancy breakage. Freire et al (2019), in a study of Protium heptaphyllum in the same fragment, observed low genetic diversity of the population. This suggests the need for further investigations and effective conservation actions in fragmented landscapes, where ecological relationships and genetic resources must be maintained.…”
Section: Resultsmentioning
confidence: 87%